Magnetically recoverable base and acid catalysts in one-pot sequential reactions without mutual destruction - Nam, Phan Thanh Son; Jones, Christopher W. (Vietnam Journal of Chemistry, 2012)
A convenient approach for carrying out different reactions requiring acid and base catalysts in one pot with recovery of each individual catalyst in its essentially pure form was demonstrated. Separation of the base CoFe2O4 magnetic nanoparticles (MNP) catalyst from the solid catalyst mixture has proved to strongly depend on the nature of the solid acid catalyst. Combining the base MNP catalyst that was magnetically recoverable with a cation exchange resin catalyst that was recovered gravimetrically, one-pot deacetalization-Knoevenagel reactions and one-pot aldehyde protection-deprotection readily proceeded with 100% conversions being achieved under very mild conditions.